Acute effect of ultrasound focused on reducing abdominal fat on body composition, metabolic parameter and cardiovascular and autonomic variables (Research, Society and Development, 2021)
Objective: To analyze the body composition, behavior of cardiovascular variables and autonomic HR modulation after a high power focused ultrasound application in women with localized abdominal fat and overweight. Methods: Twenty-three women participated (21.3 ± 3.06 years), presenting at least 1.5 cm of abdominal skin fold, using oral contraceptive and sedentary. A visit was made to the aesthetic center, where the initial anthropometric assessments were performed, and before and after the application of the therapy, the body composition (bioimpedance), blood pressure (BP) and autonomic assessment were evaluated. The indices (RMSSD, SDNN) and (HF, LF un and ms2) were analyzed. For the analysis of the effects on body composition, BP variables and cholesterol values and autonomic modulation at rest and recovery moments found in the pre and post-intervention moments, Student's t-test or Wilcoxon test were applied. with Dunn's post-test for non-normal distribution data, and effect size was calculated using Eta-squaredd and p